Potential applications of pulsed electric field in the fermented wine industry - Feng, Yuanxin; Yang, Tao; Zhang, Yongniu; Zhang, Ailin; Gai, Lili; Niu, Debao (Frontiers in Nutrition, 2022)
Fermented wine refers to alcoholic beverages with complex flavor substances directly produced by raw materials (fruit or rice) through microbial fermentation (yeast and bacteria). Its production steps usually include saccharification, fermentation, filtration, sterilization, aging, etc., which is a complicated and time-consuming process. Pulsed electric field (PEF) is a promising non-thermal food processing technology. Researchers have made tremendous progress in the potential application of PEF in the fermented wine industry over the past few years. The objective of this paper is to systematically review the achievements of PEF technology applied to the winemaking and aging process of fermented wine. Research on the application of PEF in fermented wine suggests that PEF treatment has the following advantages: 1) shortening the maceration time of brewing materials; 2) promoting the extraction of main functional components; 3) enhancing the color of fermented wine; 4) inactivating spoilage microorganisms; 5) accelerating the formation of aroma substances. These are mainly related to PEF-induced electroporation of biomembranes, changes in molecular structure and the occurrence of chemical reactions. In addition, the key points of PEF treatments for fermented wine are discussed and some negative impacts and research directions are proposed.